Perception of the Medical Students on Their Future Career in Qazvin University of Medical Sciences - Barikani, Ameneh (Glob J Health Sci, 2012)
INTRODUCTION: Young physicians have many recruitment barriers in Iran. Therefore, for planning purpose, assessment of the attitudes of medical intern students towards their future career is important. METHODS: This cross-sectional study assessed the view points of 300 medical students through a self administered questionnaire. Data were analyzed using SPSS software with P value < 0.05. RESULTS: Two hundred and forty students (80%) of the students had responded to the questionnaire. Among them, 67.5% were female with mean age of 21.7±2.4. The main factors for deciding to study in medicine were their interest (64.1%), family pressure (13.5%) and social prestige of medical career (9.8%). The mean score of attitudes was 2.3±0.6. In total, 24.5% of students demonstrated not having interest in studying medicine. The most important cause of their interest change was long duration of education (24.4%) and cost of studying in medicine (13.8%). In total, 88.6% of students had negative viewpoint towards their medical career in future. CONCLUSION: In general, the attitude of medical students toward their future career was negative.